THE CRIMINAL LAW SYSTEM IN INDONESIA FROM THE PERSPECTIVE OF PANCASILA - Abdul Ukas Marzuki (International Journal Labs, 2023)
Since the implementation of Law Number 1 of 1946, Indonesia's Criminal Code has witnessed continuous reforms in material criminal laws, formal criminal laws, and criminal law enforcement. These three components are interconnected, necessitating comprehensive reform. The 2012 Criminal Code Bill aimed at achieving sentencing goals and brought about three types of updates. The first type includes main punishments like imprisonment, cover-up punishment, supervision punishment, fine punishment, and social work punishment. The second type specifically entails the death penalty. The third type comprises additional punishments such as revocation of rights, confiscation of goods or invoices, judge's decision announcements, renewal of criminal sanctions for losses, and fulfillment of local customary obligations. Criminal punishment theories emphasize improvement and prevention from an instrumental perspective. Punishment serves as an instrument to achieve goals beyond itself, like rehabilitating offenders or protecting society. The nature of punishment must align with these objectives, rendering punishment valuable in the pursuit of those ends. However, instrumental theory also allows for alternative means if more efficient. For Indonesia, the essence of law according to Pancasila emphasizes godliness, humanity, unity, democracy, and fairness. Pancasila serves as an ethical benchmark for being a complete Indonesian human being, adhering to Indonesian laws, and guiding behavior toward others and the environment. As society evolves, the law must remain dynamic and adaptable to societal needs. An appropriate legal system in Indonesia should be grounded in the values and culture of the nation, particularly Pancasila, the nation's foundational philosophy. The national legal system must align with Pancasila's ideals to maintain harmony and justice in the Indonesian state.